Intracranial Stenting: Is It Still an Option for Treatment of Patients With Intracranial Atherosclerosis? - Abualhasan, Ahmed; Abd-Allah, Foad; Pero, Guglielmo; Sobh, Khaled; Mansour, Ossama; El-Serafy, Omar; Boccardi, Edoardo (Frontiers in Neurology, 2019)
Intracranial atherosclerotic disease (ICAD) represents a major cause of recurrent stroke and transient ischemic attacks. ICAD continues to be a disease without an effective method of reducing risk of recurrent stroke and death even with aggressive highly monitored medical treatment. We reviewed Data from three randomized controlled studies that published comparing intracranial stenting versus medical treatment for symptomatic severe ICAD. Ethnic, demographic, clinical and procedural differences were found among the data from those trials that might influence their results. Future research should aim at establishing refined selection criteria that can identify high-risk ICAD patients who may benefit from intracranial stenting.